2023
DOI: 10.1111/gcb.16659
|View full text |Cite
|
Sign up to set email alerts
|

Embracing fine‐root system complexity in terrestrial ecosystem modeling

Abstract: Earth System Models (ESMs; Box 1) grapple with low confidence in projecting the dynamics and functioning of the biosphere within the Earth system. Many efforts have been made to improve predictability regarding the structure and functions of terrestrial ecosystems since the 1970s, though this work has mostly focused on aboveground leaf and canopy processes (e.g.,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 133 publications
(193 reference statements)
0
4
0
Order By: Relevance
“…Incorporating belowground resource partitioning would allow for a more holistic differentiation between resource‐acquisitive and resource‐conservative strategies, as well as contrasting strategies for nutrient and water acquisition and drought tolerance. In addition to variable rooting depth by PFTs, increasing model capacity for root systems and functions to respond dynamically to resource changes is an ongoing challenge for vegetation models (Wang et al ., 2023). A particular challenge is posed by model structures that are not spatially explicit within grid cells and given soil layers (Table 2; the gap models reviewed are only spatially explicit aboveground), such that resource partitioning is not possible belowground and resources are shared by all members of the community.…”
Section: Introductionmentioning
confidence: 99%
“…Incorporating belowground resource partitioning would allow for a more holistic differentiation between resource‐acquisitive and resource‐conservative strategies, as well as contrasting strategies for nutrient and water acquisition and drought tolerance. In addition to variable rooting depth by PFTs, increasing model capacity for root systems and functions to respond dynamically to resource changes is an ongoing challenge for vegetation models (Wang et al ., 2023). A particular challenge is posed by model structures that are not spatially explicit within grid cells and given soil layers (Table 2; the gap models reviewed are only spatially explicit aboveground), such that resource partitioning is not possible belowground and resources are shared by all members of the community.…”
Section: Introductionmentioning
confidence: 99%
“…Leaf phenology serves as the primary indicator controlling plant growth under climatic changes (Fu et al., 2020; Wang et al., 2023; Xia et al., 2015). Extensive research has indicated that global warming advanced spring leaf unfolding and delayed autumn leaf senescence, thereby prolonging the growing season of plants (Buermann et al., 2018; Menzel et al., 2020; Peñuelas et al., 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In this issue of Global Change Biology, Wang et al (2023), propose a modelling structure of root systems, which approximates function through three functional pools—TAM, or transport roots (T), absorptive roots (A) and mmycorrhizal fungi (M). This both echoes conceptual shifts which have already occurred for both canopies (De Pury & Farquhar, 1997) and microbial pools (e.g.…”
mentioning
confidence: 99%
“…While root system representation up to now have been simple, this has not arisen out of model parsimony but rather a data bias towards aboveground processes. Wang et al, 2023, propose a functional structure to the root system with potential for reducing uncertainty in belowground function under global change, potentially testable with development of modern observational approaches. This opens the way for potential model‐led collaborations in the future.…”
mentioning
confidence: 99%